2006
DOI: 10.1111/j.1365-2788.2006.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive health assessments during de‐institutionalization: an observational study

Abstract: Background People with intellectual disability (ID) leaving institutions pass through a transition stage that makes them vulnerable to inadequate health care. They enter into community care under general practitioners (GPs) who are often untrained and inexperienced in their needs. Specifically designed health reviews may be of assistance to both them and their new GPs as they go through that phase. Methods This research aimed to investigate the effectiveness of a specially designed health review, the comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…Duplicates removed (n = 868) 4 articles reported on same study 2 articles reported on same study 108,115,116,132,138,141 ) and South Africa (n = 2 131,134 ). Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicates removed (n = 868) 4 articles reported on same study 2 articles reported on same study 108,115,116,132,138,141 ) and South Africa (n = 2 131,134 ). Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…5,6 Applying health assessments by means of questionnaires, focusing on highly prevalent diseases for people with ID, have proven to be an effective method to detect health needs, and can play an important role in health monitoring and health promotion. [7][8][9][10][11] Research has shown increased disease detection, as well as an increase in prevention and health promotion activities. [7][8][9][10] Most patients with ID valued the use of health assessment instruments positively.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Research has shown increased disease detection, as well as an increase in prevention and health promotion activities. [7][8][9][10] Most patients with ID valued the use of health assessment instruments positively. [12][13][14][15][16] In residential care in the Netherlands, medical care for people with ID is often delivered by a specialist ID physician.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation